2017
DOI: 10.1007/s00436-017-5438-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of herbal extracts used in ethno-veterinary medicine and green-encapsulated ZnO nanoparticles against Aedes aegypti and microbial pathogens

Abstract: Dengue and chikungunya are arboviral diseases mainly vectored by the mosquito Aedes aegypti. Presently, there is no treatment for these viral diseases and their prevention is still based on vector control measures. Nanopesticides fabricated using herbal extracts as reducing and capping agents currently represent an excellent platform for pest control. In this scenario, the present study assessed the acute toxicity of seven plants employed in ethno-veterinary medicine of southern India, as well as the green syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…Actually, “all natural” herbal products are mixtures of potentially biologically active ingredients without clear quantities. These ingredients may possess inherent pharmacological activities, cause unexpected herb-drug interactions and even have direct toxicities (Baig et al, 2014 ; Banumathi et al, 2017 ). Meanwhile, it is known that expressions of proteins, activities of enzymes and functions of organs would be altered in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, “all natural” herbal products are mixtures of potentially biologically active ingredients without clear quantities. These ingredients may possess inherent pharmacological activities, cause unexpected herb-drug interactions and even have direct toxicities (Baig et al, 2014 ; Banumathi et al, 2017 ). Meanwhile, it is known that expressions of proteins, activities of enzymes and functions of organs would be altered in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 75 , 136 ], and Vibrio spp. [ 101 , 129 ]. More promisingly, NPs have also been shown to inhibit antibiotic-resistant bacteria such as Methicillin-resistant S. aureus (MRSA) [ 81 , 130 ] and drug-resistant E. coli [ 123 ].…”
Section: Bactericidal Properties and Synergistic Enhancement Of Comentioning
confidence: 99%
“…Green technologies have recently been shown to be a new strategy for reducing the use of chemical pesticides since overuse has often led to massive non-target impacts and widespread resistance [9,18]. Modern study has revealed an increased level of insecticide activity in green nanoparticles (NPs) synthesized by Euphorbia rothiana [19], Cymbopogon citratus [20], Pedalium murex [21] etc. Among different NPs, Zinc Oxide nanoparticles (ZnO NPs), having nanosized morphology, have increased interest among several researchers as a result of their exclusive optical or chemical activities [22].…”
Section: Introductionmentioning
confidence: 99%